Raman analysis of gold catalyst vapor liquid solid germanium nanowires. Issue 11 (25th July 2014) - Israel, M.; Moreac, A.; Rogel, R.; Landesman, J. P.; Pichon, L.; Pizzini, Sergio; Kissinger, Gudrun
Abstract Germanium nanowires (GeNWs) were synthesized in a low pressure chemical vapor deposition reactor (LPCVD) using a vapor‐liquid‐solid process (VLS). In this work, the focus is put on the characterization of these GeNWs using scanning electron microscopy (SEM) combined with Raman spectroscopy. In particular, NWs with conical shape grown at a moderate temperature (320 °C) were investigated in terms of the intensity measured for the Ge‐related Raman line. The two main observations, discussed in this paper, are the anomalous magnitude of this line, as compared to measurements under the same conditions on a Ge(100) substrate, and the oscillations observed when the Raman line intensity is measured while scanning the laser beam along the axis of the conical shaped NWs, from the tip to the bottom. These effects are discussed involving the fact that optical modes appear in such NWs (both for the incident and Raman scattered light) when conditions on the diameter, the laser excitation wavelength, and substrate (on which the NWs are transferred after growth) are fulfilled. Taking into account these specific optical modes, the effects observed can be explained. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)